Student Sport Culture in Urban and Rural Schools: A Comparative Study in Papua - Yambedoan, Thadius; Suhartini, Bernadeta; Wasa, Carolus; Sujarwo, Sujarwo (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
This study aims to examine differences in student sport culture between urban and rural schools in Papua, focusing on cultural perceptions of the body, participation rates, and physical education curriculum implementation. A quantitative survey method was employed, involving 100 students, with 50 from urban schools and 50 from rural schools. Data were analyzed using t-tests and multiple linear regression. The results show that urban students and teachers had more positive perceptions of physical education, with mean scores of 4.2 and 4.5, compared to 3.5 and 3.8 in rural schools (t = 5.67, p < 0.001). Daily participation rates were higher among urban students (40%) compared to rural students (20%). Urban students were primarily motivated by health benefits (50%), while rural students were motivated by recreational and social aspects (40%). Recommendations include developing culturally relevant curricula, improving rural school infrastructure, providing teacher training, fostering community involvement, and integrating technology to enhance access and participation.